The Microbiology Galaxy Lab: A community-driven gateway to tools, workflows, and training for reproducible and FAIR analysis of microbial data - Nasr, Engy; Amato, Pierre; Bernt, Matthias; Bhardwaj, Anshu; Blankenberg, Daniel; Brites, Daniela; Cumbo, Fabio; Do, Katherine; Ferrari, Emanuele; Griffin, Timothy J; Gruening, Bjoern; Hiltemann, Saskia; et al. (bioRxiv, 2025)
Microbial research generates vast and complex data from diverse omics technologies, demanding innovative analytical solutions. The microGalaxy community addresses these needs with the Microbiology Lab, a user-friendly platform that integrates 290+ tool suites and 85+ curated workflows for microbial analyses, including taxonomic profiling, assembly, annotation, and functional analysis. Hosted on several public Galaxy servers (microbiology.usegalaxy.org, .eu, .org.au, .fr), it supports workflow creation & customization, sharing, and updates across public and private Galaxy servers, ensuring flexibility and reproducibility. The platform also offers 35+ tutorials, 15+ instructional videos, and structured learning pathways, empowering researchers to conduct advanced analyses. Backed by a community-driven approach, the Microbiology Galaxy Lab ensures up-to-date tools and workflows through testing and semi-automatic updates to meet global research demands. With its focus on rapid workflow prototyping and high-throughput processing, the Microbiology Galaxy Lab provides scalable resources for researchers at all expertise levels.Microbial research generates vast and complex data from diverse omics technologies, demanding innovative analytical solutions. The microGalaxy community addresses these needs with the Microbiology Lab, a user-friendly platform that integrates 290+ tool suites and 85+ curated workflows for microbial analyses, including taxonomic profiling, assembly, annotation, and functional analysis. Hosted on several public Galaxy servers (microbiology.usegalaxy.org, .eu, .org.au, .fr), it supports workflow creation & customization, sharing, and updates across public and private Galaxy servers, ensuring flexibility and reproducibility. The platform also offers 35+ tutorials, 15+ instructional videos, and structured learning pathways, empowering researchers to conduct advanced analyses. Backed by a community-driven approach, the Microbiology Galaxy Lab ensures up-to-date tools and workflows through testing and semi-automatic updates to meet global research demands. With its focus on rapid workflow prototyping and high-throughput processing, the Microbiology Galaxy Lab provides scalable resources for researchers at all expertise levels.